Estimation of CO2 Absorption, Biomass, and Carbon Deposit the Trees on the Street City of Malang - Gita Niken Madapuri; Haidar Nazarudin Azwar; Muhammad Asmuni Hasyim (Pandawa Institute, 2021)
Climate change increases the concentration of the greenhouse effect, this was caused by the lack of trees as a function of carbon sequestration. Therefore, this study aims to map the vegetation distribution in the streets of the city of Malang and to measure its carbon stocks. The used method was vegetation analysis, to calculate the estimation of biomass, carbon storage and CO2 absorption using the allometric equation Brown; Brown and Lugo; and Morikawa. The study was conducted at the street lots of traffic activity, there are six stations representing the city of Malang, those are Tlogomas Street, North of Ahmad Yani Street, Letjend Sutoyo Street, Panglima Sudirman Street, Sudanco Supriadi Street and Kolonel Sugiono Street. The results of this study are that the most carbon-absorbing tree is Albizia saman with a value of 287,656 kg and the region that absorbs the most carbon is Panglima Sudirman Street, that located in the middle of the city.